(untitled) (Journal of Economic Research & Business Administration, 2017)
The issue of creating and establishing Kazakhstan as a trade and logistics hub between Asia and Europe is on the agenda of the Government. To achieve this goal, the state program has been approved, central and local authorities, private business invests new infrastructure projects for logistics. The article discusses the relationship between the development of the national economy and transport logistic infrastructure. Also, We analyze and share the function of each cargo vehicles in the total volume of cargo of the country and implementation of the state program.As a result of analyzes of both positive and negative factors of transport infrastructure influence on economic growth.The establishment of Kazakhstan as a logistics hub will directly depend on the state of the logistics infrastructure, the quality of the service and technology used.